Detection of a high-barrier conformational change in the active site of cytochrome P450(cam) upon binding of putidaredoxin - Wei, Julie Y. (2005)
The orientation of the substrate camphor in the active site of reduced CO-bound cytochrome P450(cam) (CYP101) as a function of reduced putidaredoxin (Pdx(r)) addition has been examined by NMR using perdeuterated CYP101 and peredeuterated Pdx as well as isotopically labeled d-camphor. This permits the (1)H resonances of CYP101-bound camphor to be observed without interference from the signals of CYP101 or Pdx, and confirms assignments of the methyl signals of camphor in the bound form. The Cys(4)Fe(2)S(2) ferredoxin Pdx is the physiological redox partner and effector of CYP101. The addition of Pdx to the reduced CYP101-camphor-CO complex results in a conformational selection that is slow on the chemical shift time scale with spectral effects observed primarily at the 8-CH(3) group of the camphor. The camphor signals are ring-current shifted by the heme, and for the 9- and 10-CH(3) resonances, these shifts are reasonably well predicted by ring current calculations from the crystal structure of CO-bound CYP101. However, in the absence of Pdx the 8-CH(3) resonance of CYP101-bound camphor is observed at considerably higher field than predicted. Dynamic simulations using ring current shift restraints generated a structure with low chemical shift violations in which the hydrogen bond between the camphor carbonyl oxygen and the OH of Tyr 96 is lost, and an expansion of the active site takes place that permits reorientation of the camphor within the active site.